Sebaran Tanaman Bambu Di Blok Pemanfaatan Taman Hutan Raya Wan Abdul Rachman Provinsi Lampung - Anggiat Tamba Togatorop; Melya Riniarti; Duryat Duryat (Fakultas Kehutanan Universitas Mulawarman, 2021)
Wan Abdul Rachman Forest Park (Tahura WAR) is one of the forest areas in Lampung Province. Tahura WAR has a fairly high diversity of flora, one of which is the bamboo plant. There is not much data related to the diversity of bamboo plant species found in Tahura WAR, especially in the Utilization Block. As an effort to develop the potential of bamboo, it is necessary to conduct research on the diversity of types and distribution patterns of bamboo plants. The purpose of this study was to analyze the diversity of bamboo plants and their distribution patterns in the Tahura WAR Utilization Block. This research was conducted in May 2020 in the Tahura WAR Utilization Block, using the river transect method along the 720 m length and 4 m width. The results showed that there were four types of bamboo plants in the Tahura WAR Utilization Block, namely Gombong bamboo (Gigantochloa pseudoarundinaceae) and Tali bamboo (Gigantochloa apus), Ater Batu bamboo (Gigantochloa atter) and Betung bamboo (Dendrocalamus asper. These four species showed a level of diversity bamboo plants that are categorized as low and the distribution pattern is random.